The Effect Of Work Environment And Work Discipline On Employee Performance At PT Rekso Nasional Food Mcdonald's Edutown Tangerang Branch - Nurhaliza, Syalwa; Sunarsi, Denok (Pascasarjana Universitas Pasundan, 2025)
The purpose of this study was to determine the effect of work environment and work discipline on employee performance at PT Rekso Nasional Food, McDonald's Edutown Tangerang Branch, partially and simultaneously. The method used is quantitative. The sampling technique used saturated sampling,namely 55 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The results of this study are that the work environment has a significant effect on employee performance with a determination coefficient value of 53.4% and the hypothesis test obtained t count> t table or (7.798> 2.006). Work discipline has a significant effect on employee performance with a determination coefficient value of 37.8% and the hypothesis test obtained t count> t table or (5.569> 2.006). The work environment and work discipline simultaneously have a significant effect on employee performance with a regression equation Y = 10.099 + 0.470X1 + 0.275X2. The coefficient of determination value is 60.6% while the remaining 39.4% is influenced by other variables. The hypothesis test obtained the calculated F value > F table or (39.929 > 2.780).